Group of men playing Kabaddi - Mumbai Archive Project Team (Jio Institute, 2024)
Players prepare for a game of kabaddi near the once-famous Santoshi Mata Temple, now replaced by a huge multi-story building. Kandivli and Malad, a suburb south of Kandivli, are likely the rival kabaddi teams.